Estimating the prevalence of drawing in clinical practice among kiwi doctors. (2nd October 2022) - Kearns, Ciléin; Murton, Samantha; Oldfield, Karen; Anderson, Augustus; Eathorne, Allie; Beasley, Richard; Nacey, John; Jaye, Chrystal
Abstract: Drawing has played a key role in the development and dissemination of Medicine and Surgery, such as to share anatomy, pathology, and techniques for clinical interventions. While many of the visuals used in medicine today are created by medical illustration professionals, and by imaging techniques such as photography and radiography; many doctors continue to draw routinely in their clinical practice. This is known to be valued by patients, for example when making informed decisions about care. We surveyed doctors in New Zealand online regarding their use of drawing to explore the prevalence of this practice. 472 complete responses were obtained over 3 months. There were very high rates of drawing among responding doctors practicing in both medical and surgical specialties. Reasons for drawing are explored and included professional, collegial, and patient communication, supporting informed consent, clinical documentation, and for planning procedures. Widespread use of drawing in clinical practice, almost non-existent training or support for this in digital workflows, and high interest in resources to develop clinical drawing skills, suggest unmet training needs for this practical clinical communication tool.